2012
DOI: 10.1037/a0025511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the predictive validity of the Computerized Comprehension Task: Comprehension predicts production.

Abstract: Until recently, the challenges inherent in measuring comprehension have impeded our ability to predict the course of language acquisition. The present research reports on a longitudinal assessment of the convergent and predictive validity of the CDI: Words and Gestures and the Computerized Comprehension Task (CCT). The CDI: WG and the CCT evinced good convergent validity however the CCT better predicted subsequent parent reports of language production. Language sample data in the third year confirm this findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 33 publications
7
59
0
Order By: Relevance
“…Parents wore blackout glasses and noise-cancelling headphones to mitigate parental influence during the task. The assessment followed the protocol for the Computerized Comprehension Task (CCT; Friend & Keplinger, 2003; Friend, Schmitt, & Simpson, 2012). The CCT is an experimenter-controlled assessment that uses infants’ haptic response to measure early decontextualized word knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents wore blackout glasses and noise-cancelling headphones to mitigate parental influence during the task. The assessment followed the protocol for the Computerized Comprehension Task (CCT; Friend & Keplinger, 2003; Friend, Schmitt, & Simpson, 2012). The CCT is an experimenter-controlled assessment that uses infants’ haptic response to measure early decontextualized word knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…Pilot data using the automated version showed that children’s interest in the task waned to such an extent that attrition rates approached 85% (attrition rates using the experimenter-controlled CCT are between 5% and 10%; M. Friend, personal communication, June 17, 2014; P. Zesiger, personal communication, May 21, 2014). Therefore, to collect a sufficient amount of data to yield effects, we used the well-documented protocol of the CCT (Friend & Keplinger, 2003; Friend et al, 2012). Previous studies have reported that the CCT has strong internal consistency (Form A: α = .836; Form B: α = .839), converges with parent report (partial r controlling for age = .361, p < .01), and predicts subsequent language production (Friend et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCT also demonstrates convergent validity with MCDI reports of vocabulary comprehension and 4-month test-retest reliability (Friend & Keplinger, 2008;Friend & Zesiger, 2011) and accounts for significant variance in subsequent vocabulary production (Friend et al, 2012).…”
Section: Cctmentioning
confidence: 99%
“…The CCT contains 41 pairs of images presented on a touch-sensitive screen, following the method of Friend and colleagues (Friend & Keplinger, 2003;Friend, Schmitt, & Simpson, 2012). Children are prompted to touch the target by an experimenter ("Where is the shoe?…”
Section: Cctmentioning
confidence: 99%